GOVERNMENTAL AID AGENCIES AND NGOS' PARTNERSHIP.CASE STUDY: A CRITICAL APPRAISAL OF KOICA'S POLICY TOWARDS DEVELOPMENT NGOS. - FRANCIS, Nkengong Bamuh (The Graduate School, Ajou University, 2011)
The era in which we live is an increasingly complex one. In this complex era, a lot of challenges have surfaced and will continue to surface. These complex challenges include global terrorism, inter and intra tribal wars, spread and reemergence of diseases, climate change, global warming, persistence poverty, etc. Most of these challenges are not natural but man-made and can be overcome by the collective action of human beings and not by a single state or nation. The global approaches to tackling these problems have laid emphasis on partnership and cooperation between state and non-state actors as way forward. In response state agencies, inter-governmental organizations have entered into partnership with NGOs. OECD member countries have realized that NGOs are very instrumental in international cooperation. This is supported by the fact that they have established and implemented NGO cooperation laws while others have simply reinforced it. The Korean government through KOICA, established an NGO department in order to foster partnership and cooperation with development NGOs. The purpose of this study is to examine and make a critical appraisal on KOICA-NGO partnership based on KOICA？s policy towards development NGOs. This partnership has been a subject of criticism based on the fact that KOICA has another agenda and that KOICA is not the ？Mother Theresa？ it seems to be as its official declaration does not match the reality on the ground. KOICA simply seems to be ？a business in Mother Theresa？s clothes？. The study will also explore possible avenues on how to repair the holes in the boat carrying KOICA and its partner NGOs and pilot it to a port of common interest to both parties.
학위논문(석사)--아주대학교 국제대학원--NGO학과,2011. 1